ANALISIS PREDIKSI KEBANGKRUTAN DENGAN MENGGUNAKAN METODE ALTMAN Z-SCORE PADA PT HERO SUPERMARKET TBK TAHUN 2013-2022 - Putri, Hikmah Amanda; Nofiana, Lina (Journal of Research and Publication Innovation, 2024)
This research aims to analyze bankruptcy predictions using the Altman Z-Score metode at PT Hero Supermarket Tbk. This type of quantitative research. The analytical technique use is the Altman z-score method which uses four ratios, namely the rasio of working capital to total asset(X1), retained earning to total asset(X2), earning before interest and taxes to total asset(X3) and market value of equity to book value of total debt(X4). The results of this study indicate that PT Hero Supermarket Tbk is predicted to experience financial distress and bankruptcy during 2020-2022. In 2020 the z-score results showed a number of (2,7074), in 2021 it was (2,629), and in 2022 it showed a number of (2,1783) the z-score value in this below 1,11 in those three years and it can be concluded that PT Hero Supermarket Tbk is experience financial distress or predicted to go bankruptcy